2011
DOI: 10.1097/jpn.0b013e31821072e4
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease in Pregnancy

Abstract: This article reviews the current research on periodontal disease and treatment and its potential impact on maternal and newborn outcomes and provides recommendations for care management and prevention. These guidelines will be helpful for nurse professionals who are in a unique position to counsel pregnant women to improve the oral health of expectant mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 43 publications
0
12
0
2
Order By: Relevance
“…Therefore, pregnant women with higher risk of dental disease are less likely to receive treatment. Pregnant women may also mistakenly believe that dental problems are a usual and unavoidable experience during pregnancy [27,28]. The popular notion that the fetus takes calcium from the teeth of the mother and that dental treatments can harm the fetus still widely exist, although there is no evidence supporting them [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, pregnant women with higher risk of dental disease are less likely to receive treatment. Pregnant women may also mistakenly believe that dental problems are a usual and unavoidable experience during pregnancy [27,28]. The popular notion that the fetus takes calcium from the teeth of the mother and that dental treatments can harm the fetus still widely exist, although there is no evidence supporting them [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Dentists, generally, are not willing to treat pregnant women and may postpone dental treatments until after childbirth. However it has been confirmed that providing dental treatments in pregnancy, including prophylaxis, restorations, extractions, and periodontal management is generally safe and effective [28,32]. …”
Section: Discussionmentioning
confidence: 99%
“…Lachat et al stated that oral health information can be given to women before or during the prenatal period at the first appointment and that pregnant women can be informed about the expected physiological changes in their mouth and can participate in the prevention and alleviation of these conditions (27). The authors also stated that preventive oral health information could be included in the birth class.…”
Section: Discussionmentioning
confidence: 99%
“…A Doença Periodontal (DP) é uma afecção crônica, considerada a segunda patologia bucal na população mundial, na qual bactérias gramnegativas participam do seu processo de desenvolvimento 1,2 . Estes microrganismos anaeróbios colonizam a área subgengival causando aumento local e sistêmico das prostaglandinas e citocinas 3,4 . Assim, a DP pode ser agravada por diferentes fatores de risco, tais como o tabagismo, doenças sistêmicas e cardiovasculares, e especialmente condições sistêmicas como a gestação 5,6 .…”
Section: Introductionunclassified